Impact of engineered lignin composition on biomass recalcitrance and ionic liquid pretreatment efficiency. Issue 18 (28th June 2016) - Shi, Jian; Pattathil, Sivakumar; Parthasarathi, Ramakrishnan; Anderson, Nickolas A.; Kim, Jeong Im; Venketachalam, Sivasankari; Hahn, Michael G.; Chapple, Clint; Simmons, Blake A.; Singh, Seema
Abstract : Impact of engineered lignin composition on biomass recalcitrance. Abstract : Lignin plays important biological functions in plant cell walls, but also contributes to the recalcitrance of the walls to deconstruction. In recent years, genetic modification of lignin biosynthesis pathways has become one of the primary targets of plant cell wall engineering. In this study, we used a combination of approaches to characterize the structural and compositional features of wild-type Arabidopsis and mutants with distinct lignin monomer compositions: fah1-2 (Guaiacyl, G-lignin dominant), C4H-F5H (Syringyl, S-lignin dominant), COMT1 (G/5-hydroxy G-lignin dominant), and a newly developed med5a med5b ref8 ( p -hydroxyphenyl, H-lignin dominant) mutant. In order to understand how lignin modification affects biomass recalcitrance, substrate reactivity and lignin fractionation, we correlated these properties with saccharification efficiency after ionic liquid (IL) pretreatment. Results showed that the cleavage of β-O-4 linkages in the H- or S-lignin mutants was greater than that in G-lignin mutants. Furthermore, density functional theory (DFT) based calculations indicate higher chemical reactivity of the linkages between H- and S-lignin monomers, a possible cause of the reduced recalcitrance of H- or S-lignin mutants. Glycome profiling was conducted to study the impact of lignin modification on overall composition, extractability, integrity and lignin-associated features of most major non-cellulosic cell wall glycans in these mutants. This study provides insights into the role of lignin monomer composition on the enzymatic digestibility of biomass and the effect of lignin modification on overall wall structure and biomass pretreatment performance.